2022
DOI: 10.3390/diagnostics12061374
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in XMN1-HBG2, HBS1L-MYB, and BCL11A and Their Relation to High Fetal Hemoglobin Levels That Alleviate Anemia

Abstract: Anemia is a condition in which red blood cells and/or hemoglobin (Hb) concentrations are decreased below the normal range, resulting in a lack of oxygen being transported to tissues and organs. Those afflicted with this condition may feel lethargic and weak, which reduces their quality of life. The condition may be manifested in inherited blood disorders, such as thalassemia and sickle cell disease, whereas acquired disorders include aplastic anemia, chronic disease, drug toxicity, pregnancy, and nutritional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 92 publications
0
1
0
1
Order By: Relevance
“…Un hecho interesante es que muchos pacientes ya tenían un HF basal más alto y presentaban muchos SNPs en los genes BCL11A, HMIP (polimorfismo intergénico HbS1L-MYB) y HBG2. 31 . El gen BCL11A es un factor de transcripción que codifica una proteína de dedos de zinc y está asociado al desarrollo de varias neoplasias linfoides 32 .…”
Section: Discussionunclassified
“…Un hecho interesante es que muchos pacientes ya tenían un HF basal más alto y presentaban muchos SNPs en los genes BCL11A, HMIP (polimorfismo intergénico HbS1L-MYB) y HBG2. 31 . El gen BCL11A es un factor de transcripción que codifica una proteína de dedos de zinc y está asociado al desarrollo de varias neoplasias linfoides 32 .…”
Section: Discussionunclassified
“…Our results emphasized that the C allele was associated with the type of βmutation rather than with HbF expression in patients with HbE-β + -thalassemia. Previous studies have demonstrated that in HbE-β-thalassemia, the T allele or T/T genotype is also associated with increased HbF and milder anemia [ 6 , 41 ]. However, in our study, the T allele was identified in a relatively low proportion of patients with both low and high HbF levels ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%